Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acsnano.5b05718
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamond–Gutta Percha Composite Biomaterials for Root Canal Therapy

Abstract: Root canal therapy (RCT) represents a standard of treatment that addresses infected pulp tissue in teeth and protects against future infection. RCT involves removing dental pulp comprising blood vessels and nerve tissue, decontaminating residually infected tissue through biomechanical instrumentation, and root canal obturation using a filler material to replace the space that was previously composed of dental pulp. Gutta percha (GP) is typically used as the filler material, as it is malleable, inert, and bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 67 publications
2
95
0
Order By: Relevance
“…For example, nanodiamond-functionalized amoxicillin in combination with gutta-percha for root canal treatment can eliminate residual bacteria after root canal filling. 75 In addition, due to the proliferation of bacteria and the reduction in pH in the course of treatment, orthodontic treatment often leads to the formation of dental plaque chalk, and brackets coated with CuO and ZnO NPs can effectively inhibit the growth of S. mutans; however, the coatings also affect the appearance of the brackets. 76 Maxillofacial prostheses placed in a complex external environment containing a variety of flora have been shown to develop biofilms, thereby increasing the incidence of tissue inflammation surrounding the prostheses.…”
Section: Dental Materialsmentioning
confidence: 99%
“…For example, nanodiamond-functionalized amoxicillin in combination with gutta-percha for root canal treatment can eliminate residual bacteria after root canal filling. 75 In addition, due to the proliferation of bacteria and the reduction in pH in the course of treatment, orthodontic treatment often leads to the formation of dental plaque chalk, and brackets coated with CuO and ZnO NPs can effectively inhibit the growth of S. mutans; however, the coatings also affect the appearance of the brackets. 76 Maxillofacial prostheses placed in a complex external environment containing a variety of flora have been shown to develop biofilms, thereby increasing the incidence of tissue inflammation surrounding the prostheses.…”
Section: Dental Materialsmentioning
confidence: 99%
“…Gutta-percha is typically used as a fi ller material as it is malleable, inert and biocompatible. However, traditional gutta-percha has certain shortcomings including leakage, root canal reinfection, and poor mechanical properties 7) . Therefore, new fi llers and composites are widely being studied to overcome these issues.…”
Section: Discussionmentioning
confidence: 99%
“…It is known, that ZnO nanoparticles have selective toxicity to bacteria but exhibit minimal eff ects on human cells 6) . Moreover, it has been reported that the size and surface of carbon-based nanomaterial (nanoparticles, fullerenes, singlewalled carbon nanotubes, graphene oxide) play a signifi cant role in the antibacterial activity [7][8][9][10] . Graphite has been evaluated as a biomedical material in heart valves, biosensors and joints 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, gutta-percha (GP) reinforced with anti-bacterial NDs has been evaluated as a possible endodontic material. 44 . Because of their bio-fluorescent…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
“…Incorporation of NDs in GP has made it made possible to deliver power antibiotics to the root canal. In a recent study, Lee et al 44 successfully incorporated NDs bound to amoxicillin (NDamoxicillin) into GP and observed that not only the composite ND-GP exhibited enhanced bactericidal properties against Streptococci via prolonged drug release but increased Young's modulus, tensile strength and yield strength were also observed. 44 This study maybe the first of many which could lead to development of endodontic materials that not only can deliver antibiotics to the canal but also carry regenerative growth factors to enhance root and pulpodentine regeneration.…”
Section: Endodontic Treatment and Regenerative Endodonticsmentioning
confidence: 99%